Reflections on the Pedagogical Foundations in Counselor Education - Eric R Baltrinic; Carrie Wachter Morris (Teaching and Supervision in Counseling, 2020)
In this article, we provided a summary and concluding remarks to this special edition on signature pedagogies in counselor education. We summarized contributing authors’ perspectives and considerations for bolstering the profession’s discussion on teaching and pedagogical foundations. Focusing on how contributing authors assessed and used the concept of signature pedagogies to facilitate the broader discussion on pedagogical foundations, we posed reflections and offered considerations for future instructional research in counselor education.
Keywords: signature pedagogies; pedagogical foundations; teaching; counselor education; instructional research